IFC Annual Report 2017 : Creating Markets - International Finance Corporation (Washington, DC, 2017)
The International Finance Corporation (IFC) and the Multilateral Investment Guarantee Agency (MIGA), two institutions focused on private sector development, are leading our efforts to create markets and crowd in private sector investment in developing countries. For six decades, IFC has been at the leading edge of mobilizing private capital for development, which will be essential to achieve the Sustainable Development Goals. With the knowledge that have accumulated over sixty years, IFC is uniquely placed to give the private sector a central role in financing and delivering development solutions. The scale of this ambition, together with IFC’s objective of doing more in the poorest countries, requires a new strategic framework, based on new analytical and financial tools and approaches, which IFC is now rolling out. In the FY17 context of strengthening growth and improving market conditions in developing economies, IFC delivered a record 19.3 billion US dollars in financing to private companies in seventy five countries. This year, IFC launched the world’s biggest green-bond fund dedicated to emerging markets. In FY17, sixty three percent of IFC’s advisory program was delivered to clients in IDA countries and twenty percent in fragile and conflict-affected areas, while twenty six percent was climate-related. In addition, almost a third of new advisory projects included a focus on gender impact in project design. IFC continues to innovate beyond the successful loan syndications and investments by IFC Asset Management Company in private equity. Through strong partnerships with the private and public sectors, IFC can enhance its power to create markets and improve the lives of millions of people.